Documentación narrativa de experiencias pedagógicas. (2004)
In this work it is exposed the convenience and the theoretical and practical potentialities of clocurnenting the school  experiences, as a way of strengthening pedagogically to the schools and the teachers; as well as to investigare and to  reconstruct narratively their knowledge, words and ways of feeling. Also show the narrative documentation as tool to register what happens in the school communities and to their actors  when they design and they take ahead pedagogic experiences.